Edukasi Pertolongan Pertama pada Luka Ringan di SDN Wates 02 - Usman Bayu Prihantara; Desi Wulandari; Rika Oktavia Hartari; Dyah Pramesti Mustikasari; Laely Ayu Candra Sasqia; Fatmawati, Dilla; Dwi Maryani Devi Rohmawati; Devi Riana Putri; Farah Fauzia Zahra; Melyna Putri Viola (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
This study aims to develop an educational program on providing relief for minor injuries at SDN Wates 02. Minor injuries are common occurrences that require proper handling to prevent infections and further complications. However, a lack of knowledge and skills in administering first aid for minor injuries can lead to more serious health problems. The research method used is a developmental study with a qualitative approach. Data were collected through training sessions conducted for grade V students at SDN Wates 02 by the service team from the KSR SUB UNIT PGSD FIPP UNNES. An educational program was developed that includes information about various types of minor injuries, proper handling measures, and the importance of maintaining hygiene. The program also involves hands-on demonstrations and simulations of minor injury situations. These simple steps make it easier for students to master and understand how to perform first aid for minor injuries. The results of the training showed that this educational program was effective in improving the knowledge and skills of grade V students at SDN Wates 02 in providing first aid for minor injuries. This program successfully attracted enthusiastic participants, raising awareness about the significance of proper treatment for minor injuries and providing a solid foundation for dealing with daily injuries. Therefore, to optimize this program, it is recommended to conduct regular evaluations and updates to ensure that the information and knowledge provided are always in line with the latest developments in providing relief for minor injuries. Additionally, collaboration between schools and other parties, such as medical personnel, is also necessary to enhance the effectiveness of this educational program.